2021
DOI: 10.1159/000514945
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Localized Vulvar Pain with Neural Therapy: A Case Series and Literature Review

Abstract: <b><i>Background:</i></b> Localized vulvar pain (LVP) is a common condition among fertile women, with physical and psychosexual implications. Treatment is complex with limited benefits. Neural therapy is a regulatory therapy that uses injections of local anesthetics in low concentrations in specific points to treat different conditions. <b><i>Case Presentation:</i></b> We present the cases of 5 women, ages 33–44 years, with LVP treated with procaine 0.5% injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…A sample with 45 patients is rather heterogenous concerning the comorbidities, such as HSV, and lichen sclerosus, and yields small subgroups of primary versus secondary vulvodynia. Yet the sample is larger than the studies of McDonald & Rapkin 23 with 32 patients, and Rey-Novea 31 with five patients. In our study, we prospectively included all consecutive cases of vulvodynia in the respective period.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…A sample with 45 patients is rather heterogenous concerning the comorbidities, such as HSV, and lichen sclerosus, and yields small subgroups of primary versus secondary vulvodynia. Yet the sample is larger than the studies of McDonald & Rapkin 23 with 32 patients, and Rey-Novea 31 with five patients. In our study, we prospectively included all consecutive cases of vulvodynia in the respective period.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast to the repeated application of injections on defined nerves, for example the impar ganglion 42 or the pudendal nerve, 23 , 24 we performed an individual-based regimen, with different nerve blockades depending on the progress of therapy effects, and on the individual symptoms of the respective patient. Rey-Novea et al 31 successfully treated women with localized provoked vulvodynia using a simple technique of local injections. There needs to be further investigation to see if this technique is also applicable in a mixed cohort with women with generalized, or spontaneous pain as in our patient group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LISWT, 48 ESWT, 38 and treatment with itraconazole 57 may be considered, as well as botulinum toxin A injections in the m. levator ani , which significantly reduced vulvar pain in women with vulvodynia refractory to conventional treatment 58 . Prospective study 74 and case series 79 showed promising results of therapy with local anesthetics to reduce vulvar pain in women with vulvodynia; well‐designed studies evaluating this intervention are needed.…”
Section: Discussionmentioning
confidence: 99%